Fundamentals of nursing : standards & practice - DeLaune, Sue C.; Ladner, Patricia K. (Singapore : Delmar Cengage Learning, 2006)
"This clinical learning tool contains the step-by-step actions for every procedure found in Fundamentals of Nursing: Standards and Practice, third edition, by Sue C. DeLaune and Patricia K. Ladner." -- Publisher.
Keywords: NURSNG